Prevalence of Mental Illness in the Community (TAJ: Journal of Teachers Association, 2011)
This is a cross sectional-descriptive study which was conducted in one urban mahalla and two rural mauza of Dhaka district. Self reporting questionnaire (SRQ) was applied on 327 adult respondents and structured clinical interview for diagnosis (SCID-NP) was applied on every second SRQ positive and every fourth SRQ negative respondent. The prevalence of neurotic disorders, major depressive disorder and psychotic disorders was 7.0% (7/1000 population), 4.0% (40/1000 population) and 1.2% (12/1000 population) respectively. The prevalence of psychiatric disorder was found higher in female 13.9% than male 10.2% and in middle and lower socio-economic class. The study would be helpful in future community survey on mental health and in formulating national mental health program and facilitating their effective implementation.   doi: 10.3329/taj.v19i1.3163 TAJ 2006; 19(1): 18-23